Analisis Konfirmatory Faktor Pengukuran Indikator Kesejahteraan Rumah Tangga - Yulhendri Yulhendri; Nora Susanti (Jurnal Ilmiah Econosains, 2017)
Level Measurement of household welfare require multidimensional measurement. Based on the consideration of population specification and the distribution of population residence location, this research is determined by using multistage random sampling technique. The analysis tools usedis Lisrel 8.30 to get the CFA. This study aims to determine indicators of household welfare in physical and psychological aspects. The indicators that were analyzed are physical factors, safety factor, affection, appreciation and self-actualization. The results of this study indicated that the measurement factors sourced from physical well-being consistently can be used as a measurement of household welfare level. The measurementcan be used in aspects of production factors, income level, housing conditions, home facilities, health conditions, rice adequacy, protein adequacy,water adequacy, availability of transportation facilities. While the non-physical factors which can also be used as a measurement of welfare are a sense of security in preference to public order, anxiety and fear, the role of the head of the household in maintaining the household. A sense of affection is related to the affection of the household, mutual trust, belonging, and hospitality. Meanwhile, the reward factor does not qualify to be a measurement. Self-actualization can be in the form of participation and caring for others, obedience in paying zakat, and sedeqah. Keywords: Household Welfare, Love, actualitation, assets phisik